ANALISIS KELAYAKAN USAHA DAN RISIKO PRODUKSI USAHATANI NILAM - Gilang Kurniawan; Masyhuri Mahfudz; Bambang Siswadi (Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2019)
ABSTRACTThis study aims to analyze business feasibility and analyze the factors that influence the risk of patchouli farming production in Trenggalek Regency. The data used are primary data from observations and interviews conducted in October-November 2018 in Tanggaran Village, Jombok Village, and Pakel Village, Pule District, Trenggalek Regency with samples used, a number of 45 patchouli farmers. The data analysis technique uses R/C ratio calculation analysis and Cobb-Douglass multiple linear regression. The results of the study show that the average R/C Ratio obtained is Rp. 1.54 which means every Rp. 1 fee will generate revenue of Rp. 1.54, patchouli farming is still feasible. Production risk analysis shows the variables of urea are risk-inducing factors, while season dummies are risk reduction factor. There needs to be assistance with the use of production inputs and agricultural insurance that can provide protection to patchouli farmers in anticipation of production risks.Keywords: patchouli, farming, feasibility, production risk.